Bioremediation of water recirculation in white shrimp culture using autochthonous microbiota of red mangrove - Torres, W. (2018)
The aquaculture activity in the white shrimp culture using recirculating water deteriorates the quality of the water by the hydrodynamic action of watermetabolites- organic matter, which generate negative impacts on the production of the crustacean. The objective of this research is to demonstrate that the autochthonous microbiota extracted from the red mangrove stimulates bioremediation. For this purpose, the microbiota was subjected to a process of bioaugmentation that enriches its biodiversity, so that when used, it guarantees bioremediation activity. The application of the treatment begins with the diagnosis of water quality in the different stages of the process, through the monitoring of toxic compounds such as ammonium, nitrites and nitrates and the evaluation of microbial biodiversity using metagenomic techniques such as the Reaction Test of the Polymerase, Electrophoresis in DNA testing and sequencing using the ILLUMINA technique. The results reveal that the toxic parameters maintain optimum levels of quality with the application of the microbiota composed of 1780 microbial species. Statistically it was demonstrated the significant decrease of levels of toxic compounds that the hypothesis proves, that the red mangrove microbiota acts efficiently in the bioremediation of water in the white shrimp culture.